Influence of methanol and water extracts of orange peel on stability of refined palm kernel oil (Bangladesh Journal of Scientific and Industrial Research, 2015)
The antioxidative effect of methanol and water orange peel extracts on Refined Palm Kernel Oil (RPKO) stored for twelve months at room temperature (270C-330C) was determined by monitoring the colour, refractive index, free fatty acid (FFA), acid value (AV) and peroxide value (PV). The oil was dosed with different concentrations (200 ppm to 1000 ppm) of the extracts and butylatedhydroxytoluene (BHT) (Cone. 200 ppm. The colour and refractive index of RPKO containing the extracts ranged between 11.0-13.0 units and 1.458-1.460 respectively whereas the colour and refractive index of RPKO with no additive (0 ppm) and 200 ppm BHT were 10.0 units and 1.460 accordingly. Free fathy acid (FFA) and acid value (AV) of RPKO containing methanol and water orange peel extracts were lower than RPKO containing 200 ppm BHT and they were significantly different at P